2010
DOI: 10.3109/00207454.2010.539308
|View full text |Cite
|
Sign up to set email alerts
|

Visual Memory Errors in Parkinson's Disease Patient With Visual Hallucinations

Abstract: The occurrences of visual hallucinations seem to be more prevalent in low light and hallucinators tend to be more prone to false positive type errors in memory tasks. Here we investigated whether the richness of stimuli does indeed affect recognition differently in hallucinating and nonhallucinating participants, and if so whether this difference extends to identifying spatial context. We compared 36 Parkinson's disease (PD) patients with visual hallucinations, 32 Parkinson's patients without hallucinations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Some studies have reported deficits that are specific to visual — as opposed to verbal — memory 46 . Greater memory deficits have also been found for black-and-white visual stimuli than for coloured visual stimuli, perhaps reflecting more-limited encoding of visually impoverished stimuli in patients with visual hallucinations 47 . A transitive inference test thought to measure hippocampal function has uncovered impairments in patients with PD psychosis 48 .…”
Section: Mechanisms and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported deficits that are specific to visual — as opposed to verbal — memory 46 . Greater memory deficits have also been found for black-and-white visual stimuli than for coloured visual stimuli, perhaps reflecting more-limited encoding of visually impoverished stimuli in patients with visual hallucinations 47 . A transitive inference test thought to measure hippocampal function has uncovered impairments in patients with PD psychosis 48 .…”
Section: Mechanisms and Risk Factorsmentioning
confidence: 99%
“…Tests purporting to measure visuospatial function, such as the Benton judgement of line orientation and the Rey complex figure test, are often included in test batteries for PD psychosis, but tend not to show significant differences 46,49 (although see Katzen et al 50 for evidence of deficits on the Benton test). The lack of consistent findings could be a test sensitivity issue, as other measures of visuospatial function — for example, the Visual Object and Space Perception (VOSP) number location subtest 47,51 — have been shown to differ between patients with and without visual hallucinations. Tests examining motion, spatiotemporal aspects of visual perception, and eye movements in the PD psychosis spectrum have not been reported to date, but are of particular relevance given the hypothesized role of dysfunctional motion perception and eye movement control in passage and presence hallucinations.…”
Section: Mechanisms and Risk Factorsmentioning
confidence: 99%
“…Previous studies suggest that VH in LBD are associated with structural brain abnormalities, evident in brain imaging, mainly in frontal, parietal, and occipitotemporal areas (Pezzoli et al, 2017). Other studies including patients with LBD reported an association between VH and specific cognitive deficits, including visual perception/construction, visual attention, memory, and executive functioning (Barnes and Boubert, 2011;Cagnin et al, 2013;Grossi et al, 2005;Hepp et al, 2013;Koerts et al, 2010;Manganelli et al, 2009). However, findings are often inconsistent and even contradictory, suggesting the need for further research to widen our current knowledge of the neuroanatomical and neuropsychological correlates of this symptom.…”
Section: Introductionmentioning
confidence: 99%
“…We compared hippocampal volume, shape, gray matter microstructure, and functional connectivity in individuals with PD with and without visual hallucinations, and healthy controls (HC). We also compared visuospatial memory function in each group because this ability depends upon the hippocampus (Dupret et al 2010 ) and impaired visuospatial function is, in turn, linked to visual hallucinations (Barnes and Boubert 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Visuospatial memory impairment has been reported in those with PD and visual hallucinations (Barnes and Boubert 2011 ), as well individuals with dementia with Lewy bodies (Hamilton et al 2008 , 2011 ). Visuospatial memory relies heavily upon the hippocampus (Dupret et al 2010 ) and is thought to contribute to visual hallucinations (Barnes and Boubert 2011 ). Therefore inter-relationship between hippocampal pathology postulated and this critical cognitive faculty was examined (Robbins et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%